Analisis Nilai-Nilai Pendidikan Islam Dalam Pelaksanaan Tradisi Ratib Pada Masyarakat Kota Tidore - Baharudin Baharudin; Nurmala Buamona; Asmiraty Asmiraty; Hendra Mubin; Rifda Tomagola (Jurnal Ilmiah Wahana Pendidikan, 2023)
According to M. Amin Faarouq and Burhanuddin Abdul Kadir Ratib, we don't only meet in the city of Tidore, but we can find them in several cities such as Aceh, Banten, Java, Maluku and Ternate. Especially in the city of Tidore, ratib continues to exist until now because the community considers ratib not a tradition born and separate from religion, but ratib is an Islamic religious tradition so that people believe that ratib is one of the practices, if someone has a celebration that pleases thanksgiving to enter the house, people die and even to avoid disaster, the community does ratib. The values contained in the ratib are inseparable from Islamic values. According to Muhajir, values can be hierarchically grouped into two parts, namely; first, divine values which consist of ubudiyah values and mu'amalah values. Second, insaniyah ethical values which consist of rational, social, individual, biovistical, economic, and political values and aesthetic values.